Perspectives on the receipt of a COVID-19 vaccine: A survey of employees in two large hospitals in Philadelphia. Issue 12 (19th March 2021) - Kuter, Barbara J.; Browne, Safa; Momplaisir, Florence M.; Feemster, Kristen A.; Shen, Angela K.; Green-McKenzie, Judith; Faig, Walter; Offit, Paul A.
Abstract: Background: Health care personnel have been identified by the ACIP as a priority group for COVID-19 vaccination. We conducted a survey in November-December 2020 at two large, academic hospitals in Philadelphia to evaluate the intention of hospital employees to be vaccinated. Methods: The survey was sent electronically to all employees (clinical and nonclinical staff) at a children's hospital and an adult hospital. The survey was voluntary and confidential. Questions focused on plans to receive a COVID-19 vaccine when available, reasons why employees would/would not get vaccinated, when employees planned to be vaccinated, vaccine safety and efficacy features that would be acceptable, and past history of receipt of other vaccines by the employee and family. Responses were analyzed using univariate and multiple logistic regression methods. Results: A total of 12, 034 hospital employees completed the survey (a 34.5% response rate). Overall, 63.7% of employees reported that they planned to receive a COVID-19 vaccine, 26.3% were unsure, and 10.0% did not plan to be vaccinated. Over 80% of those unsure or unwilling to be vaccinated expressed concerns about vaccine side effects and the vaccines' newness. In multivariable logistic regression, persons planning to take a COVID-19 vaccine were more likely to be older, male, more educated, Asian or White, up-to-date on vaccinations, without direct patient contact, and tested for COVID-19 in the past. No significant difference in intention to be vaccinated was found between those with higher versus lower levels of exposure to COVID-19 patients or the number of previous exposures to patients with COVID-19. Conclusions: While the majority of hospital employees are planning to receive a COVID-19 vaccine, many are unsure or not planning to do so. Further education of hospital employees about the safety, efficacy, and value of the currently available COVID-19 vaccines is critical to vaccine acceptance in this population.